PENGARUH MODEL PROBLEM BASED LEARNING DALAM MENGEMBANGKAN KEMAMPUAN BERPIKIR KRITIS SISWA KELAS V MATA PELAJARAN IPAS DI MI ROUDLOTUL ULUM GEDANGAN - Kholifatul Ismaya; Ida Latifatul Umroh; Moh Vito Miftahul Munif (Ilmuna: Jurnal Studi Pendidikan Agama Islam, 2026)
This take a look at aimed to have a look at the impact of the hassle-based totally getting to know (PBL) version on the vital wondering abilties of 5th-grade college students in the nature and Social Sciences (IPAS) concern at MI Roudlotul Ulum Gedangan. The take a look at hired a pre-experimental one-group pretest-posttest layout with a sample of 24 college students selected through the saturated sampling technique. The research instrument was a important questioning capabilities take a look at inclusive of five questions based totally on Ennis's signs; the instrument changed into demonstrated (calculated r: 0.728–0.796 > desk r: 0.404) and established dependable (Cronbach's Alpha = 0.813). facts evaluation concerned a paired-sample t-take a look at and Cohen's d effect length evaluation. The outcomes imply that the PBL version had a widespread effect on college students' essential wondering abilties, with a importance fee of 0.000 (< 0.05) and a calculated t-fee of -12.699 (df = 23). The suggest essential questioning score elevated with the aid of 5.9167. The importance of the PBL version's effect was widespread, with a Cohen's d price of 0.78. The essential wondering signs showing the best improvement have been "basic aid" (+1.96) and "inference" (+1.58). consequently, the PBL version is recommended as an alternative method for IPAS education to foster vital questioning talents among students in Madrasah Ibtidaiyah (Islamic standard faculties).